Rethinking evolution, entropy and economics: A triadic conceptual framework for the maximum entropy principle as applied to the growth of knowledge - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2010)
Recently, the maximum entropy principle has been applied to explain the evolution of complex non-equilibrium systems, such as the Earth system. I argue that it can also be fruitfully deployed to reconsider the classical treatment of entropy in economics by Georgescu-Roegen, if the growth of knowledge is seen as a physical process. Relying on central categories of Peirce's theory of signs, I follow the lines of a naturalistic evolutionary epistemology. In this framework, the three principles of Maximum Entropy (Jaynes), Maximum Power (Lotka) and Maximum Entropy Production can be arranged in a way such that evolution can be conceived as a process that manifests the physical tendency to maximize information generation and information capacity. This implies that the growth of knowledge is the dual of the process of entropy production. This theory matches with recent empirical research showing that economic growth can be tracked by measures of the throughput of useful work, mediated by the thermodynamic efficiency of the conversion of exergy into useful work.
Keywords: B52; D80; Q57; 330; Peirce; Georgescu-Roegen; maximum entropy; maximum power; natural selection; semeiosis; physical inference devices; economic growth; useful work; Entropie; Evolutionsökonomik; Wissenstransfer; Neue Wachstumstheorie; Theorie